2008
DOI: 10.1158/0008-5472.can-07-6494
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Activation of Natural Killer CellsIn vitroby a Human Dendritic Cell Vaccine

Abstract: Recruitment of circulating natural killer (NK) cells into inflamed lymph nodes is known to provide a potent, IFN-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 48 publications
(46 reference statements)
6
94
0
Order By: Relevance
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
mentioning
confidence: 74%
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
mentioning
confidence: 74%
“…They Correspondence: Dr. Sam K. P. Kung e-mail: Sam.Kung2@med.umanitoba.ca acquire specific chemokine surface receptors during development and maturation [2,[10][11][12][13][14][15]. Chemokine receptors such as CCR7, CCR5, and CXCR3 are involved in the preferential migrations and localization of NK cells into the LNs [8,[16][17][18][19], whereas NK cells reside in blood, liver, and spleen exhibit higher CXCR1 and CX 3 CR1 expression [8,9,[20][21][22][23][24][25]. Nonchemokine family proteins such as chemerin and SIP 5 are also involved in the regulation of NK-cell trafficking [26,27].…”
mentioning
confidence: 99%
“…A line of evidence indicates that NK cells can regulate DC function and that NK-DC cross-regulation plays an important role in dictating the quality and the quantity of the adaptive immune responses (16)(17)(18)(19)(20)(21). A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21).…”
mentioning
confidence: 99%
“…A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21). The important role of DC in initiation and maintenance of T cell responses to chlamydial infection has been demonstrated by several previous studies using mouse models of C. trachomatis mouse pneumonitis strain, more recently called Chlamydia muridarum (22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%